The efficacy of periodised resistance training on neuromuscular adaptation in older adults - Conlon, Jenny A; Newton, Robert U; Tufano, James J; Peñailillo, Luis E; Banyard, Harry G; Hopper, Amanda J; Ridge, Ashley J; Haff, G Gregory (European journal of applied physiology, 2017)
PURPOSE: This study compared the effect of periodised versus non-periodised (NP) resistance training on neuromuscular adaptions in older adults. METHODS: Forty-one apparently healthy untrained older adults (female = 21, male = 20; 70.9 ± 5.1 years; 166.3 ± 8.2 cm; 72.9 ± 13.4 kg) were recruited and randomly stratified to an NP, block periodised (BP), or daily undulating periodised (DUP) training group. Outcome measures were assessed at baseline and following a 22-week resistance training intervention (3 day week-1), including: muscle cross-sectional area (CSA), vertical jump performance, isometric and isokinetic peak torque, isometric rate of force development (RFD), and muscle activation. Thirty-three participants satisfied all study requirements and were included in analyses (female = 17, male = 16; 71.3 ± 5.4 years; 166.3 ± 8.5 cm; 72.5 ± 13.7 kg). RESULTS: Block periodisation, DUP, and NP resistance training induced statistically significant improvements in muscle CSA, vertical jump peak velocity, peak power and jump height, and peak isometric and isokinetic torque of the knee extensors at 60 and 180° s-1, with no between-group differences. Muscle activity and absolute RFD measures were statistically unchanged following resistance training across the entire cohort. CONCLUSIONS: Periodised resistance training, specifically BP and DUP, and NP resistance training are equally effective for promoting increases in muscular hypertrophy, strength, and power among untrained older adults. Consequently, periodisation strategies are not essential for optimising neuromuscular adaptations during the initial stages of resistance training in the aging population.
Keywords: kosterní svaly; Female; Training model; ženské pohlaví; svalová kontrakce; Resistance Training; Health; svalová síla; lidé; fyziologická adaptace; Aged, 80 and over; Muscle, Skeletal; Muscle Strength; Male; Aged; Adaptation, Physiological; Elderly; senioři nad 80 let; senioři; mužské pohlaví; Muscle Contraction; sarkopenie; Sarcopenia; Adaptation; odporový trénink; Humans